Exploring Accounting Students’ Understanding of Zakat Accounting Concepts and Reporting at Lamappapoleonro University - Nurmilasari Nurmilasari; Andi Zulfayani; Utari Lukman (GENTARA: management and accounting research, 2025)
This research aims to explore accounting students' understanding of zakat accounting concepts and reporting, specifically for students in the Accounting program at Lamappapoleonro University. The findings are intended to provide input for curriculum development and enhance the quality of accounting graduates. This study employed a descriptive qualitative approach. Data was collected through an open-ended questionnaire distributed online via Google Forms to 22 students from the Accounting Study Program at Lamappapoleonro University.The results indicate that accounting students at Lamappapoleonro University have a reasonably good understanding of zakat accounting concepts and their financial reporting. However, there is still a need for improvement, particularly in the implementation aspect and in gaining a deeper understanding of complex zakat accounting treatments and their reporting in accordance with the latest standard, PSAK 409